Assessment of chemoreceptivity in goldfish (Carassiusauratus) fingerlings to identify natural food attractants for feed formulation - Lim, Crystal Li Ying (2018)
Goldfish (Carassiusauratus) is one of the popular choice of fish hobbyist among the ornamental fish and usually kept in large numbers in aquarium or ponds. Thus type of feed and feeding routine are crucial to prevent overfeeding that will lead to the pollution of the aquarium. The assessment of chemoreceptivity in goldfish fingerlings was conducted to determine the chemoreceptivity between commercial fish pellet and the live feed. The aim was to suggest a formulation for the best diet using live food supplementation as feed attractants added to commercial pellet. In this experiment, the feeding behaviour of the goldfish were recorded using GoPro recorder for 15 minutes after feeding them with six different pairs of feed formulation. Findings showed that the average time spent on bloodworm was the longest, followed by brine shrimp and mosquito larvae, while commercial pellet was the shortest. In addition, the highest frequency of number of entries preferred were for bloodworm, brine shrimp, mosquito larvae and commercial pellet accordingly. As a conclusion, the current study has indicated highly significant results from the time spent (P=0.001) and the number of entries (P=0.000) in each compartments, thus the goldfish was more receptive to the live fresh feed as compared to the commercial fish pellets as hypothesised.